2017
DOI: 10.1071/ah16003
|View full text |Cite
|
Sign up to set email alerts
|

Differences in risk and protective factors for workplace aggression between male and female clinical medical practitioners in Australia

Abstract: Objectives. The aim of the present study was to investigate differences in prevalence, as well as risk and protective factors, for exposure to workplace aggression between male and female clinicians in Australian medical practice settings.Methods. In a cross-sectional, self-report study in the third wave of the Medicine in Australia: Balancing Employment and Life survey (2010-11), 16 327 medical practitioners were sampled, with 9449 (57.9%) respondents working in clinical practice. Using backward stepwise elim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Exposure rates in nursing have been consistently very high in Australia over a 35-year period (Hegney, Eley, Plank, Buikstra, & Parker, 2006;Holden, 1985;O'Connell et al, 2000;Shea et al, 2017), but are quite possibly increasing, particularly from co-workers. It must be acknowledged, however, that prevalence rates and impacts are known to vary across health professionals' personal and professional characteristics, and different workplaces and specialties (Guay, Goncalves, & Jarvis, 2014Hegney et al, 2006;Hills, 2017;Hills et al, 2012;Shea et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure rates in nursing have been consistently very high in Australia over a 35-year period (Hegney, Eley, Plank, Buikstra, & Parker, 2006;Holden, 1985;O'Connell et al, 2000;Shea et al, 2017), but are quite possibly increasing, particularly from co-workers. It must be acknowledged, however, that prevalence rates and impacts are known to vary across health professionals' personal and professional characteristics, and different workplaces and specialties (Guay, Goncalves, & Jarvis, 2014Hegney et al, 2006;Hills, 2017;Hills et al, 2012;Shea et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence of broader organisational and government efforts to address the high levels of workplace aggression experience by health workers in Australia. A range of prevention and minimisation measures has been established in health workplaces, both private and public, but the available evidence suggests that even some of the most readily implemented have not been adopted, are not effectively implemented or do not offer the protections that might have been expected (Hills, 2017;Hills & Joyce, 2014;. In the State of Victoria, responding to the findings of the Violence in Healthcare Taskforce Report (Violence in Healthcare Taskforce, 2016), the State Government has recently announced a range of initiatives in an "Australian first policy to prevent violence in hospitals" (Hennessy, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SVAs in the workplace consist of physical violence, robbery, armed robbery, sexual touching, sexual assault, and death threat (Guay et al, 2016). Studies on workplace exposure to SVAs have shown that men are commonly more likely to be victimized, but nuances exist concerning the sector within which they work and the type of acts sustained (Santana and Fisher, 2000;Guay et al, 2015;Hills, 2017;van Reemst and Fischer, 2016). According to a recent systematic review (Guay et al, 2015), men are more at risk in healthcare, in social work, in retail, and service industry settings, whereas women working in law enforcement and transportation professions were more often victimized than their male counterparts.…”
mentioning
confidence: 99%
“…Psychosocial factors have traditionally been considered for their impact on workers' job stress and mental health [17], while less attention has been paid to the potential of certain psychosocial working conditions to be directly involved in the dynamic of third-party workplace violence, which may be-at least in part-a side effect of a poor psychosocial work environment [18,19]. Therefore, the present study was designed with the main aim of assessing the role of psychosocial working conditions in reports of workplace violence from patients and their family members, building on the idea that violence is frequently an escalated outcome of demands from patients and their family members, which at times may be excessive and unrealistic [20,21]. Specifically, a violent episode may develop from the inadequate management of patients' demands, which may be significantly impacted by poor psychosocial working conditions fueling job stress and reducing the effectiveness of healthcare workers' job performance.…”
Section: Introductionmentioning
confidence: 99%